Mān on the Referentiality Continuum in Thai - Kaenmuang, Jinawat; Piyamahapong, Piroon; Pittayaporn, Pittayawat (Journal of the Southeast Asian Linguistics Society)
Pronouns are traditionally defined as a pro-form of an explicit antecedent. However, the pronoun mān in Thai sometimes occurs without any co-referring explicit nominal expression, leading previous studies to consider them as non-referential. This study argues that, despite the absence of an explicit antecedent, such instances of mān have implicit referents that are inferable from context. One thousand instances of mān functioning as subject or object from the Thai National Corpus were analyzed in a usage-based approach. They were categorized according to their referentiality using three criteria: explicitness of a nominal antecedent, concreteness of a antecedent, and inference of a referent. The analysis reveals that the referentiality of the pronoun mān is not dichotomous but instead lies on a continuum in which one end expresses semantic referentiality with an explicit antecedent with a higher level of referent concreteness, and the other expresses pragmatic referentiality with an implicit antecedent with a lower level of referent concreteness. Additionally, different types of referential expressions–verb phrases, clauses, and discourse–and ambiguous cases among them strongly support the notion of gradience of referentiality.